21 Effect of jinjiang granules on intestinal mucosal immunity in mice model. (5th December 2017) - Miao, MS; Cao, LH; Qiao, JY; Zhang, R
Abstract : Objectives: To study the effect of Jinjiang granules on immune function in mice with hypoimmunity and to provide a basis for the application of Jinjiang granules in the early stage of clinical colds. Methods: KM mice (half male, half female) were randomly divided into 6 groups. The mice were given the drug once a day (normal control group and model group were given with physiological saline). The mice were weighed once every 3 days. Weight was adjusted to the drug volume. All the groups except the normal group were injected with cyclophosphamide to establish the mice model of hypoimmunity for 3 days. On the seventh day, two hours later the thymus, spleen and intestinal mucosa were obtained after intragastric administration to detect SIgA, Gln, TNF-α and IL-1β. Results: The mice models of hypoimmunity in mice succeeded. In the medication group the IL-1β and TNF-α levels improved and the SIgA and Gln levels were reduced to different degrees. In the treatment group there was a certain therapeutic effect on spleen and thymus tissue pathological changes. The best curative effect is the lentinan, followed by large dose of jinjiang group and medium dose of jinjiang group. Conclusions: Jinjiang granules can improve the immune function of the mice models of hypoimmunity. It also improves intestinal immune function. It prevents colds when given as the initial medicine. Acknowledgements: The Central Plains scholars (162101510003), the team of outstanding scientific and technological innovation in Henan province (TCJ2014-391), Henan University of Traditional Chinese Medicine and deep processing of geoherbs Collaborative Innovation Centre (2012)188–2.